Distal convoluted tubule sexual dimorphism revealed by advanced 3D imaging - Tahaei, Ebrahim; Coleman, Richard; Saritas, Turgay; Ellison, David H.; Welling, Paul A. (American journal of physiology. Renal physiology, 2020)
The thiazide-sensitive Na + -Cl − cotransporter (NCC) is more abundant in kidneys of female subjects than of male subjects. Because morphological remodeling of the distal convoluted tubule (DCT) is dependent on NCC activity, it has been generally assumed that there is a corresponding sexual dimorphism in the structure of the DCT, leading to a larger female DCT. Until now, this has never been directly examined. Here, optical clearing techniques were combined with antibody labeling of DCT segment markers, state-of-the-art high-speed volumetric imaging, and analysis tools to visualize and quantify DCT morphology in male and female mice and study the DCT remodeling response to furosemide. We found an unexpected sex difference in the structure of the DCT. Compared with the male mice, female mice had a shorter DCT, a higher cellular density of NCC, and a greater capacity to elongate in response to loop diuretics. Our study revealed a sexual dimorphism of the DCT. Female mice expressed a greater density of NCC transporters in a shorter structure to protect Na + balance in the face of greater basal distal Na + delivery yet have a larger reserve and structural remodeling capacity to adapt to unique physiological stresses. These observations provide insight into mechanisms that may drive sex differences in the therapeutic responses to diuretics.